2017
DOI: 10.23956/ijermt/v6n4/123
|View full text |Cite
|
Sign up to set email alerts
|

The Indian Scenario of Corporate Social Responsibility

Abstract: Abstract:overnment of India provided guidelines for implementation of CSR in industries it helps the developing country like India to assist it in meeting social and environmental standards. The CSR approach is holistic and integrated with the core business strategy. CSR has gone through many phases in India. India has become the only country in the world with legislated corporate social responsibility. Now a day the increasing awareness about CSR & changing environment forces the companies to contribute for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Other studies, e.g. Loura (2014), Nejati and Sasan (2012), Wankhade (2014), Muafi (2016), Moustafa Abdelmotaleb, and Saha (2018) were conducted by using a small sample size. These authors suggested that further studies use a large sample size to be able to generalise the findings.…”
Section: Sample Size and Data Typementioning
confidence: 99%
“…Other studies, e.g. Loura (2014), Nejati and Sasan (2012), Wankhade (2014), Muafi (2016), Moustafa Abdelmotaleb, and Saha (2018) were conducted by using a small sample size. These authors suggested that further studies use a large sample size to be able to generalise the findings.…”
Section: Sample Size and Data Typementioning
confidence: 99%